Pengaruh Kemiringan Posisi Modul Surya Prototipe 200 WP Dengan Tracking System Terhadap Energi Listrik Yang Dihasilkan - Syarif Hidayat; Agung Hariyanto; Ridha Yasser (KILAT, 2019)
The use of solar modules in converting solar energy into electrical energy is something interesting to study. In this case the 200 WP solar module is used as an experiment to see the symptoms produced during a certain time. The material of the solar module is silicon oxide crystal (SiO2). The process of converting solar energy into electricity can be affected by the angle between the rays that come with the solar module field. If the position of the solar module does not change throughout the day, this angle depends on the position of the sun or time. In this case, it is necessary to study how the angle that produces the most electricity is adjusted to the change in time in one day. The energy produced by solar tracking systems is more optimal than that of solar modules in an immovable state. Changes in the position of the solar module should be done once every half hour with a slope angle of +50 from the initial position of the clock change. At the position of the solar module is not moving, the maximum power is at 12:30 a.m. which is 5.129 watts